IMPROVING TEACHER ABILITY IN DEVELOPING SCIENTIFIC BASED RPP AT UPT SD NEGERI PLUMBANGAN 01 - Siswati; Isna Nurul Inayati (EBTIDA': Jurnal Pendidikan Dasar Islam, 2022)
Analysis of the quality report cards for SD Negeri Plummbang 01 in 2020 shows that there are weaknesses in the standard process that is being implemented. One of the weaknesses that occur in this process standard is related to the teacher's ability to develop scientific-based learning implementation plans. Referring to this condition, it is necessary to conduct school action research to improve competence first in the preparation of scientifically based lesson plans. This type of research is school action research. This research was carried out at SD Negeri 01 Plumbangan in November 2021 with the research subjects being all teachers at SD Negeri 01 Plumangan. The technique of collecting data from this school action research is through qualitative data obtained from observation/observations, interviews and document studies. This procedure includes the following stages: (1) planning, (2)implementation, (3) observation, and (4) reflection. Based on the results of reflection, monitoring and evaluation that have been carried out, it can be concluded that cycle 1 and cycle 2 activities have increased so that all objectives of the school action researchactivities are declared successful.